Pengaruh Produk Pembiayaan BMT terhadap Usaha Mikro Nasabah - Nurhidayati Islamiah; A. Nur Achsanuddin (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2020)
This study aims to determine the effect of Mudharabah and Murabahah financing products on the increase in micro-businesses of customers in Makassar. This type of research used in this research is quantitative. The data processed is mudharabah and murabahah financing customers obtained from Baitul Ma Wat Tamwil Multi Jasa Sejahtera City of Makassar. The analysis technique used in this research is the simple regression analysis technique. to determine the effect of the independent variable on murabahah financing on the dependent variable on the development of SMEs and the independent variable for the independent variable on the independent variable for the development of SMEs which were tested separately. Based on the results of data processing, it shows that murabahah and mudharabah financing has a positive influence on the development of SME customers of BMT Multi Jasa Sejahtera.